Novelirani instituti delniškega prava glede upravljavske in kapitalske strukture ter uveljavljanja pravic manjšinskih delničarjev in upnikov - Kocbek, Marijan (Podjetje in delo, 2015)
The author discusses the amended institutes brought forth by the amendment ZGD-1I to Slovenian Companies Act regarding management and capital issues and the exercise of rights of minority shareholders and creditors. The author highlights the changed regulation regarding the enforcement of the liability of management and supervisory bodies, which emphasizes the protection of minority shareholders. He points out that the amendment does not include the original proposal of enacting the business judgment rule, which has already been established in the domestic case law. The amendment ZGD-1I brings significant new rules regarding the functioning and powers of the supervisory boards related to the audit and the audit committee. As an optional possibility it also codifies the so-called internal audit. With regard to capital issues the author highlights the new regulation which allows the possibility of determining the price of shares in their public issue founded on the so-called "Book Building". The author assesses positively the limitation of the amount of the conditional increase in the subscribed capital to 10% when this corporate operation is used for the purposes of realization or issuing of stock options for management, supervisors or workers of public limited companies. The amendment ZGD-1I features many other changes which complement various individual corporate institutes, with the goal of contributing to a more effective exercise of the rights of minority shareholders and emphasizing the protection of creditors in corporate relations.
Keywords: delniške družbe; nadzorni organi; odškodninska odgovornost; revizija; vodenje